A Telehealth-Based Adolescent Health Service Integration Model for Improving Health Knowledge and Health Behavior: Systematic Review - Mega Setiawan; Yenni Ariestanti; Suryanih; Dewi Nawang Sari; Endang Siti Mawarni (Journal of Scientific Insights, 2026)
Adolescent health services are crucial components of public health due to adolescents’ greater vulnerability to physical, mental, reproductive, and social health disorders. However, evolving digital technology has spurred greater use of telehealth services, which have been associated with better access and effectiveness of adolescent health services. The present systematic review was conducted to assess an integrated telehealth-based adolescent health service model and its efficacy in improving adolescents’ health knowledge and behavior. This review was conducted according to Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines. The articles were searched in the PubMed, Scopus, and BioMed Central (BMC) databases from 2016 to 2026 using the following keywords: telemedicine, digital health, adolescent health services, health knowledge, and online interventions. Inclusion criteria were English- or Indonesian-language full-text articles on the implementation of telehealth services for adolescents. Quantitative and mixed-methods, cohort, quasi-experimental, and systematic review studies were selected. In all, 254 articles were included, and, after screening and eligibility assessments, 10 were selected. Results indicated that the telehealth intervention positively affected mental health, social participation, smoking cessation, healthcare access, medication adherence, and adolescent engagement with health services. The interventions were mobile health applications, online counseling, telemedicine, remote monitoring, and virtual support platforms. Digital accessibility, healthcare provider support, multidisciplinary collaboration, and digital health literacy supported successful implementation. But internet limitations, communication barriers, and low digital literacy posed obstacles. Generally, telehealth-based adolescent health services enhance adolescents’ existing knowledge, psychosocial well-being, and health behaviors in the digital age.